2008
DOI: 10.1007/s00167-008-0572-4
|View full text |Cite
|
Sign up to set email alerts
|

Saphenous nerve block is an effective regional technique for post-menisectomy pain

Abstract: In this study we have evaluated the post menisectomy pain relief offered by Saphenous nerve block. This study was planned on 40 patients with a pre-operative and post operative diagnosis of medial meniscus lesion undergoing partial menisectomy arthroscopically. Patients were randomized into 2 groups where Group I received a preoperative Saphenous block while group 2 did not receive a peripheral block, but received 1 ml of saline as placebo injection. After blocks both groups received general anesthesia and IV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 17 publications
3
63
1
1
Order By: Relevance
“…Femoral nerve blockade has a low risk of complications including short-term quadriceps dysfunction, femoral neuritis and residual numbness. 13,14 Saphenous nerve blockade has to date only been assessed in patients treated by arthroscopic partial menisectomy 15 but is being studied currently to assess its suitability for patients undergoing TKA (ClinicalTrials.gov identifier NCT01333943). Further studies could therefore assess patients for objective and subjective sensory changes after the use of saphenous and femoral nerve blocks in comparison with those treated without nerve blocks for postoperative analgesia.…”
Section: Resultsmentioning
confidence: 99%
“…Femoral nerve blockade has a low risk of complications including short-term quadriceps dysfunction, femoral neuritis and residual numbness. 13,14 Saphenous nerve blockade has to date only been assessed in patients treated by arthroscopic partial menisectomy 15 but is being studied currently to assess its suitability for patients undergoing TKA (ClinicalTrials.gov identifier NCT01333943). Further studies could therefore assess patients for objective and subjective sensory changes after the use of saphenous and femoral nerve blocks in comparison with those treated without nerve blocks for postoperative analgesia.…”
Section: Resultsmentioning
confidence: 99%
“…21,22 A previous study on arthroscopic medial meniscectomy using landmark techniques for a more distal approach to the saphenous nerve block showed a greater clinical effect in the reduction of NRS scores when compared with our study. 5 Nevertheless, we hypothesize that this larger clinical difference in pain score reduction was due to three important methodological differences: 1) subjects were not given intraoperative opioids; 2) subjects were not given preemptive multimodal analgesia; and 3) surgeons did not inject the arthroscopic port sites with local anesthetic. In our view, some, if not all, of these methods are becoming common practice and should be incorporated into any investigation that looks at differences in clinical outcomes for this surgery.…”
Section: Discussionmentioning
confidence: 98%
“…16 Using several prior studies on similar surgical procedures, our power analysis assumed a baseline NRS score of 5 without a peripheral nerve block. 5,17,18 Therefore, in order for our study to detect a 40% reduction in NRS pain scores between groups immediately postoperatively, 24 subjects per group were required to provide the necessary power (90%) for this study. One additional patient per group was enrolled to account for patient drop-out or loss to follow-up.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 It can also be utilized independently for procedures involving only the medial aspect of the distal leg. 2 In a recent study, Benzon et al compared the success rates of five different non-ultrasound approaches to the saphenous nerve block (perifemoral, transsartorial, block at the medial femoral condoyle, below-the-knee field block, and blockade at the level of the medial malleolus), and they found that the transsartorial approach was best able to provide sensory blockade to the medial aspects of the leg and foot, with a success rate of 100% for the medial leg and 80% for the medial foot (n = 10). 3 The use of ultrasound has recently been advocated as a means to facilitate the administration of the saphenous nerve block.…”
Section: Résumémentioning
confidence: 99%